EARLY DEBRIDEMENT IMPROVES OUTCOME IN MANAGING ANKLE TUBERCULOSIS: A SYSTEMATIC REVIEW - Gunawan, Indra (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2023)
Background: Around 16% of the 7.5 million incident cases worldwide in 2019 were extrapulmonary tuberculosis (EPTB) cases. Only 1–4% of all occurrences of osteoarticular TB occur in patients with EPTB, a highly rare condition that causes a kind of ankle or foot arthritis. Chronic synovitis is the predominant symptom of early-stage ankle TB. Although certain circumstances necessitate surgical intervention, conservative therapy is still vital. This study aims to determine whether early surgery for ankle TB impacts the results. Methods: A systematic search strategy was conducted across several electronic reference databases (PubMed, Cochrane Library, ProQuest) and included articles published between 2017–2022. Duplicate publications, review articles, and incomplete articles were excluded Result: Database search yielded a total of 86 articles, which were systematically eliminated, leaving 5 relevant articles. Analyzed articles showed that combining chemotherapy and surgery effectively manages ankle tuberculosis. Conclusion: Early debridement is advised to enhance ankle TB management results. A combination of chemotherapy, surgery, and non-weight bearing is the effective treatment method.